DESAIN BUKU RESEP MASAKAN KHAS PARIAMAN “SAJIAN MINANGKABAU” - Asrinaldi, Dra. Zubaidah A, M.Sn, Dra. Syafril R, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
Abstrack- Pariaman has specialities have not been widely known by the general public outside West sumatera. The purpose of this final work was designing distinctive cookbooks Pariaman as media promotion so that the typical cuisine of Pariaman, better known by the public, the process of designing non Pariaman in the design of this book is to use procedures that are descriptive. The process of data collection is done by observation, interviews, and analyzed documentation. by using SWOT analysis. The book is the right media as media promotion of the typical cuisine of Pariaman, media it contains information about the materials, tools and how to Cook several different types of cuisines and accompanied by cooking tips. The merit of this book is to be copied, can permanently be reread as well as practical. The making of a recipe book cooking is done with software computer and print process. This book also has some media advocates as a support of promotion such as posters, banners, billboards, calendars, paper bags, handbook, stickers, mugs, ashtrays and key chains. By using this book as a primary medium and some media used as a means of supporting the promotion of the typical cuisine recipes Pariaman was expected to be known by the public at large and has survived, so that it can maintain the culture of Indonesia. Keywords : Buku resep ,Masakan khas Pariaman, Desain, Sajian Minangkabau